VOCATIONAL HIGH SCHOOL TEACHERS DIFFICULTIES IN IMPLEMENTING ASSESSMENT CURRICULUM 2013 IN TEACHING WRITING - Lia Lesmanasari (Journal of English Education Program (JEEP), 2020)
This study deals with the investigation of vocational high school teachers difficulties in implementing assessment curriculum 2013 in teaching writing. It is a descriptive qualitative study in one of the vocational high school in Banjar. In conducting this study the writer used qualitative research in which descriptive study was employed to collect the data from participant in this research, that was an English teacher in vocational high school who implemented assessment in curriculum 2013. Moreover, classroom observation and interview were the instruments used by the writer in collecting the data.  The data obtained from those instruments were analyzed by the writer qualitatively. Based on the data from classroom observation, the teacher implemented ongoing assessment in various ways including homework, class discussion, communicating purposes and learning targets, journal, portfolios, questioning, self-assessment and peer assessment as suggested by Stiggins (2005, p. 26). It means that the teacher implemented ongoing assessment in writing assessment in the contex of curriculum 2013. Furthermore, that the teacher has difficulties in implementing curriculum 2013 such as in developing content, the idea, and the features of curriculum 2013. The strength of curriculum 2013 consisted of some points. First, 2013 curriculum uses a scientific approach.  Second, 2013 curriculum is competency and character based curriculum. Third, many fields of study related to the development of skills which are more appropriate to use the competency approach. On the other hand, the weakness of curriculum 2013 is the competencies which are required in accordance with the development of society, such as character education, environmental awareness, approaches and teaching methods, the balance of soft skills and hard skills, as well as the entrepreneurial spirit, have not been accommodated in the curriculum. Keywords: Vocational high school, assessment, curriculum 2013, writing assessment